Collectivism: Interpreting the Perception of the Appearance of Health Service Retribution in Community Health Center in Central Lombok Regency - Masdiani, Dewi; Pituringsih, Endar; Putra, I. Nyoman Nugraha Ardana (International Review of Management and Marketing, 2018)
The purpose of this study is to measure perceptions or interpretation of health personnel retribution management officers to their activities. this study focused on exploring the meaning of the other side of levy of health service management. The research approach used in this research is qualitative approach with case study method and interpretive paradigm. Data obtained from the results of in-depth interviews with informants. The results show that the actors who manage the levy feel what they do solely for the sense of humanity arising from togetherness in a community. In the narrow collectivist framework, actors feel that what they are doing is a form of solidarity or form of responsibility towards the other members of their group. According to the researchers the actors tend to take fraud action, viewed from the perspective of collectivity culture that lives within the organization of the Community Health Center. Keywords: Perception of Actors, Levy of Health Services, Collectivism. JEL Classifications: H2, M4